2020
DOI: 10.1002/ps.6089
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry pollen as a source of UV‐B protection ingredients for the phytoseiid mite Neoseiulus californicus (Acari: Phytoseiidae)

Abstract: BACKGROUND A new physical control method using ultraviolet‐B (UV‐B) lamps and light‐reflecting sheets (UV method) significantly suppressed a spider mite population on greenhouse strawberries. Although UV‐B radiation may adversely affect the survival of phytoseiid mites, previous research has suggested that Neoseiulus californicus can improve its survival on exposure to UV‐B irradiation by consuming antioxidants contained in tea and peach pollen. In this study, we evaluated strawberry pollen as an alternative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, recent studies have shown that under nighttime UV irradiation, N. californicus eggs survive higher daily UV‐B doses than T. urticae eggs because of a shorter egg stage, which reduces the cumulative UV‐B dose for eggs 23–25 . Moreover, a pollen diet increases UV‐B resistance of N. californicus , probably because of the antioxidants it contains 22,26 . Therefore, we hypothesized that a combination of the UV method and phytoseiid mite application would effectively control T. urticae .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent studies have shown that under nighttime UV irradiation, N. californicus eggs survive higher daily UV‐B doses than T. urticae eggs because of a shorter egg stage, which reduces the cumulative UV‐B dose for eggs 23–25 . Moreover, a pollen diet increases UV‐B resistance of N. californicus , probably because of the antioxidants it contains 22,26 . Therefore, we hypothesized that a combination of the UV method and phytoseiid mite application would effectively control T. urticae .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Moreover, a pollen diet increases UV-B resistance of N. californicus, probably because of the antioxidants it contains. 22,26 Therefore, we hypothesized that a combination of the UV method and phytoseiid mite application would effectively control T. urticae. Because N. californicus females have been reported to rapidly escape UV-B radiation, 27 we predicted that phytoseiid mites would more frequently enter leaf areas shaded from UV-B radiation, where spider mites survive.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Biological control agents can be effective for the management of strawberry pests when used preventatively or on the condition that there is early detection and intervention. 18,19 An exception is found for the specialist strawberry aphid Chaetosiphon fragaefolii, a major strawberry pest worldwide. 20,21 This aphid species causes both direct plant damage and indirect plant damage by transmitting viruses such as mild yellow-edge virus (SMYEV), strawberry crinkle cytorhabdovirus (SCV), and strawberry mottle virus (SMoV) that reduce plant vigour and negatively impact yield.…”
Section: Introductionmentioning
confidence: 99%
“…Growing concern over the intensive use of agrochemicals and their undesirable side‐effects has promoted interest in integrated pest management (IPM) programs that include the use of biological control agents as a complement or an alternative to agrochemicals 15–17 . Biological control agents can be effective for the management of strawberry pests when used preventatively or on the condition that there is early detection and intervention 18,19 . An exception is found for the specialist strawberry aphid Chaetosiphon fragaefolii , a major strawberry pest worldwide 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, pollen was one of the most extensively studied alternative food in previous studies. Some research recently proved that pollen protected the predators from UV‐B and enhanced their survival under hot and dry environments (Urbaneja‐Bernat & Jaques, 2021; Yuan et al, 2021). In agricultural systems, pollen sometimes is available in the flowing season of crops and do not require any extra investment.…”
Section: Introductionmentioning
confidence: 99%